Development of grit scale for junior high school - จิดาภา ศิริพรรณ (สำนักทดสอบทางการศึกษาและจิตวิทยา มหาวิทยาลัยศรีนครินทรวิโรฒ, 2022)
This research aims to develop and verify the quality of Grit scale for junior high school. The sampling in this research consisted of 830 junior high school students under Office of the Basic Education Commission in Bangkok by using Stratified Random Sampling method. The implemented Grit scale consisted of 25 situational multiple-choice questions with four choices. The Grits scale for junior high school had an IOC from 0.60 -1.00, item discrimination from 0.20 or more, internal consistency of 0.84 and after checking for construct validity of the test by Second Order Confirmatory Factor analysis, found that the model of Grit developed by the researcher conformed with the empirical data (Chi-Square=24.33 df=29 p=0.71 GFI=0.99 AGFI=0.99 RMR=0.01 RMSES=0.00)